2018
DOI: 10.1002/adfm.201804688
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progresses in Phototherapy‐Synergized Cancer Immunotherapy

Abstract: Cancer immunotherapy has recently gained much attention in the search of cancer cure due to its ability to "train" the immune system in seeking out and removing residual tumor cells. However, relying on cancer immunotherapy alone may fail to ablate primary tumors. Phototherapy is a promising modality that offers an elegant solution to eradicate tumors through the simple application of light irradiation and meanwhile triggers immune responses by immunogenic cell death to enhance antitumor immunity. Uniting phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
199
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(199 citation statements)
references
References 164 publications
0
199
0
Order By: Relevance
“…To identify the role of Cu 2− x Te NEs in activating antitumor immunity, we fabricated bilateral tumors at the right and left flanks of mice, and they were were designated as the primary and distant tumors, respectively (Figure a) . The results display that the maturation ratio of dendritic cells was promoted from 9.7 % to 18.6 % after treatment with the Cu 2− x Te NEs (Figure b; see Figure S23).…”
Section: Resultsmentioning
confidence: 99%
“…To identify the role of Cu 2− x Te NEs in activating antitumor immunity, we fabricated bilateral tumors at the right and left flanks of mice, and they were were designated as the primary and distant tumors, respectively (Figure a) . The results display that the maturation ratio of dendritic cells was promoted from 9.7 % to 18.6 % after treatment with the Cu 2− x Te NEs (Figure b; see Figure S23).…”
Section: Resultsmentioning
confidence: 99%
“…SPECT Imaging: Mice bearing 4T1 tumor models were i.v. injected with 200 µci of 125 I-HOPA-C18PMH-PEG or 125 I-HOPA-C18PMH-PEG/PL and imaged by small animal SPECT/CT imaging system at different time points (1,4,6,12,24,48, and 72 h). All experiments were conducted in compliance with all relevant ethical regulations.…”
Section: Methodsmentioning
confidence: 99%
“…Radiotherapy (RT) including radioisotope therapy (RIT) and external beam radiotherapy (EBRT) have been widely applied in clinic for cancer treatment . In order to improve the therapeutic efficiency of cancer, RT usually combines other therapies such as chemotherapy, photothermal therapy, or surgery for cancer treatment, further increasing the cure rate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] There are many kinds of materials has been synthesized for cancer imaging and therapy. [13] As drug carriers, 2D nanomaterials could facilitate endocytosis. [14] Previous studies revealed that zeolitic imidazolate framework-8 (ZIF-8) could be generated by a coordination reaction between 2-methylimidazole (Hmim) and Zn 2 + in aqueous phase, [15] in which the molar concentration of Hmim is much higher than that of Zn 2 + .…”
mentioning
confidence: 99%